Brandt-Daroff exercise among elderly with vertigo - Masruroh, Siti Handariatul; Suhariyanti, Enik; Priyanto, Sigit (Innovation in Health for Society, 2022)
Vertigo may harm the patients; however, many vertigo sufferers are less concerned about dizziness. The only action taken is taking medication when vertigo recurs and lying down or resting at home. Efforts to reduce vertigo symptoms non-pharmacologically include therapy Brandt-Daroff, which can accelerate vertigo recovery and prevent recurrence without taking drugs. This study aims to apply the therapy Brandt-Daroff to relieve vertigo symptoms in the elderly in the family. The method used in this research is a case study with a purposive sampling technique. The sample was an elderly patient aged 49 years who experienced vertigo with a pain scale of 4. The research data was taken by the participatory observation method. Interview and documentation method. This study found that physical therapy Brandt-Daroff can reduce vertigo symptoms in the form of pain from a scale of 4 to a scale of 2 within six visits for two weeks. Brandt-Daroff exercise minimises the scale of pain that can be done at home. Keywords: Vertigo; nursing care; community nursing; Brand-Daroff exercise; pain scale